Leadership and authority in Central Asia : an Ismaili community in Tajikistan - Mastibekov, Otambek (London : Routledge, 2014)
'This book explores the unfolding of world history in a remote corner of Central Asia: the region of Badakhshan. The history of this region has commonly been explored through the lens of the major superpowers who competed over its territory in the nineteenth and twentieth centuries, including Britain, Russia, and China. Here, we are offered a comprehensive overview of the history of the Ismaili community in Tajikistan. Leadership and Authority in Central Asia identifies traditional forms of religious authority within the network of religious functionaries at a range of levels and discusses the functions of Ismaili political leaders as they have evolved through time. Skilfully applying an interdisciplinary approach -- drawing on historical sources, including unpublished materials, and ethnographic fieldwork data collected through interviews -- and a perceptive analysis of political theories of leadership in communist and post-communist societies, this book challenges the ways religious and secular categories have been distinguished in recent scholarship. Developing a structural explanation for the survival and evolution of religious and political authorities of Badakhshani Ismailis in times of radical social and political upheaval, this book will be of interest to scholars of Muslim societies, Political Science and Central Asian Studies'--
Originally presented as the author's thesis (doctoral)--University of London, 2010.
Includes bibliographical references : pages 162-176 and index.
Keywords: Ismailites -- Tajikistan -- Kuhistoni Badakhshon -- History; Political leadership -- Tajikistan -- Kuhistoni Badakhshon -- History; Islam and state -- Tajikistan -- History; Kuhistoni Badakhshon (Tajikistan) -- History